Kebijakan Pendidikan Ramah Bertangan Kidal di Universitas Islam Negeri Sumatera Utara Medan - Mardianto Mardianto; Makmur Syukri; Irwan S (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The aims objectives of the study are 1) to examine the extent to which the policy of North Sumatra State Islamic University Medan towards left-handedness, 2) to prepare strategic policies in order to fulfill left-handed facilities and infrastructure, and 3) to facilitate left-handed students in conducting lecture activities in the classroom. The research method uses qualitative research methods with a phenomenological approach, which is an approach or search to explore and understand a central phenomenon. This research was conducted on campuses I, II, III and IV UIN North Sumatra Medan. The number of participants in this study were 30 people consisting of 9 lecturers, 3 educators and 18 students. This research was conducted from May – July 2021. Based on the results of the research that has been carried out, 3 important themes were obtained that reflect the condition of the facilities that do not pay attention to left-handed individuals, namely 1) Consideration of left-handed friendly facilities, 2) Campus facilities are not left-handed friendly, and 3) Barriers arising related to facilities that are not left-handed friendly. With this research, the rectorate can use the results of this research as a reference source in making left-handed-friendly planning as early as possible, both in the form of procurement of lecture facilities and when collecting student data based on the website.